CORRELATION OF THE NUMBER OF IMAGES OF AN N-POINT GRAVITATIONAL LENS AND THE NUMBER OF SOLUTIONS OF ITS SYSTEM - Kotvytskiy, A. T.; Bronza, S. D.; Shablenko, V. Yu. (Одеські астрономічні публікації, 2017)
In this paper, we study the correlation between the number of solutions of a system of lens equations and the number of source images that a gravitational lens has. We defined the concept of an image in a gravitational lens. To find the set of solutions of a system of lens equations, we applied methods of algebraic geometry.